ENTERPRISE MANAGEMENT SYSTEM AND THE ROLE OF INFORMATION-ANALYTICAL SUPPORT WITHIN IT (Development Service Industry Management, 2024)
The article examines the definition of the concept of "management system" by various authors, the main components of a management system, and explores approaches to the classification of management systems and their types based on classification features. It concludes that, according to certain classification features, management systems at various levels, objects, and scales are subsystems of the general enterprise management system. However, others—such as the nature of interaction with the external environment and the nature of the control action—may or may not be inherent to management subsystems.The article also considers the structural elements of an enterprise management system, namely: the controlling and controlled subsystems, the target, functional, scientific-methodological, and support subsystems, as well as the role and place of information-analytical support within the management system. Information-analytical support is a component of the support subsystem, which in turn consists of methodological, informational, legal, resource, and technical-technological support. Thus, information-analytical support encompasses the methodological, informational, legal, and technical-technological components. Additionally, since information is often regarded as a resource, it also includes the resource component.The article explores the role of information-analytical support in managing internal processes and its influence on the degree of impact of the external environment. Directions for future research prospects are identified.
Keywords: management system; classification of management systems; structure of enterprise management systems; information-analytical support